On the Marital Bond: Between Foucault and Kant - Rojas Peralta, Sergio Esteban (2025)
The text presents some of the relations that Foucault maintained with Kant's philosophy starting with the text ‘What is the Enlightenment?’. This text condenses two important elements for Foucault, the problem of authority and the different uses of reason (public and private), which he does not fail to return to in various texts, both in the 1960s and in the late 1970s and early 1980s. Kant's response is also in line with Biester’s text on the need for an authority to sanction marriage. In the 1960s, Foucault takes up the question of marriage again, analysing it under the matrix of regulating sexuality, the offspring of the bourgeois class and its patrimony. It both regulates and liberates the class from the rules of the 18th century. Subsequently, he returns to the question of the government of the self, which implies the use of reason.